2016
DOI: 10.5603/cj.a2015.0077
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of serum copeptin levels in an acute pulmonary embolism

Abstract: D-dimer (r = 0.315, p = 0.003) and troponin I (r = 0.300, p = 0.004) and inversely correlated with arterial oxygen saturations (r = -0.533, p < 0001). When the correlation of copeptin with right ventricular dysfunction parameters was investigated, it was significantly inversely correlated with the tricuspid annular plane systolic excursion (r = -0.521, p < 0.001) and positively cor related with right to left ventricle ratio (r = 0.329, p = 0.024). Copeptin (OR 1.836, p = 0.008) (Cardiol J 2016; 23, 1: 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 32 publications
8
27
1
1
Order By: Relevance
“…In our study, copeptin values of patients with RVD were significantly higher than those of patients without RVD (P < 0,05). In a similar study 12 published during the course of our study, it was found that copeptin levels in acute PE patients with RV dysfunction were significantly higher than patients without RV dysfunction, which was consistent with our results. We also found the AUC value as 0.82, the specificity as 69.6% and the sensitivity as 83.0% in ROC curve analysis for the ability of copeptin to detect right ventricular dilation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, copeptin values of patients with RVD were significantly higher than those of patients without RVD (P < 0,05). In a similar study 12 published during the course of our study, it was found that copeptin levels in acute PE patients with RV dysfunction were significantly higher than patients without RV dysfunction, which was consistent with our results. We also found the AUC value as 0.82, the specificity as 69.6% and the sensitivity as 83.0% in ROC curve analysis for the ability of copeptin to detect right ventricular dilation.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in this study, the AUC value of copeptin for PE diagnosis was found to be 0.84, while sensitivity was 68.1% and specificity was 83.7%. 12 Given the fact that copeptin is thought to be released by many physiological and pathological stimuli such as pain, hypoglycemia, hypoxemia, stroke, infection and shock; it is also expected to be high in acute PE patients. We think that factors such as pain, hypoxia and haemodynamic changes in acute PE cause increase in neurohumoral activity leading to the release of copeptin.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers determined that copeptin >17.95 pmol/L levels predicted complicated clinical course (CCC) with a specificity of 49.5% and a sensitivity of 100% while the AUC values for the copeptin in predicting CCC was 0.811 (95% CI: 0.676‐0.927). In a study conducted by Kalkan et al, it was reported that the group including patients with acute PE had higher levels of copeptin compared to those without acute PE (7.76 ± 4.4 vs 3.81 ± 1.34 ng/mL; P < 0.001) . The ROC analysis showed that copeptin levels >4.84 ng/mL had a 68.1% sensitivity and 83.7% specificity for the diagnosis of acute PE in this study.…”
Section: Discussionsupporting
confidence: 57%
“…The cut‐off of serum copeptin level was 24 pmol/L for prognostic value in PE patients in two study, and also as 7.8 ng/mL in our study . In addition, the cut‐off value of copeptin level was 4.84 ng/dL for the diagnostic predictor in another study . The differences of copeptin’s cut‐off value may be caused by unit differences and different patient population.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation